Improvement of straight-run diesel fuel low-temperature properties on the zeolite catalyst; Catalytic Hydroprocessing In Oil Refining (STS-HydroCat - 2021) - Bogdanov I. A. Ilya Aleksandrovich (2021, 2021)
Title screen